Leading Sector Analysis in Gunung Mas Regency - Sasa Sasa; Sunaryo N Tuah; Wiwin Zakiah (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2022)
This study aims to find out which economic sectors are the leading sectors in Indonesia, to know the structure of the regional economy, to find out the development of the leading economic sectors and to find out which sectors have potential sectors in Gunung Mas Regency. The analysis tools used are Location Quotient Analysis, Shift Share, Klassen Typology and Growth Ratio Model. From the results of the analysis it can be concluded from the four analytical tools: (1) the results of the Location Quotient analysis, namely the Agriculture, Forestry and Fisheries Sector, the Construction Sector, the Food and Drink Accommodation Provision Sector, the Information and Communication Sector, the Real Estate Sector, the Service Sector Companies, the Government Administration Sector, Defense and Compulsory Social Security, the Education Services Sector, and the Health Services and Social Activities Sector which are the leading economic sectors in Gunung Mas Regency, Central Kalimantan Province. (2) The results of the Shift Share analysis are that there is no shift in the economic structure in Gunung Mas Regency. (3) The results of the Klassen Typology, namely the Advanced and Rapidly Growing Sector (Quadrant I) in Gunung Mas Regency are the Agriculture, Forestry and Fisheries Sector, the Mining and Quarrying Sector, the Construction Sector and the Information and Communication Sector. (4) The results of the analysis of the Growth Ratio Model, that the Potential sector is the Wholesale and Retail Trade Sector; Car and Motorcycle Repair, Real Estate Sector, Government Administration Sector, Defense and Compulsory Social Security, Health Services and Social Activities Sector